Long‐term survival analysis of patients with primary Sjögren's syndrome in China: A multicenter retrospective cohort study - Yueting, Li; Lin, Qiao; Jian, Xu; Xinwang, Duan; Yongfu, Wang; Weiguo, Xiao; Xiaodan, Kong; Qin, Li; Songlou, Yin; Liyun, Zhang; Lijun, Wu; Chanyuan, Wu; et al. (International journal of rheumatic diseases, 2024)
Aim This study aimed to evaluate the long‐term survival, causes of death, and prognostic factors in Chinese patients with primary Sjögren syndrome (pSS). Methods We included patients with pSS registered in the Chinese Rheumatism Data Centre between May 2016 and December 2021, and collected baseline clinical, laboratory, and treatment data. Survival and standard mortality rates were calculated using general population mortality data. Factors related to mortality were identified using Cox proportional hazards regression. Results Among the 8588 patients included, 274 died during a median follow‐up of 4.0 years. The overall standardized mortality ratio was 1.61 (95% CI: 1.43–1.81). Overall survival rates were 98.2% at 5 years and 93.8% at 10 years. The predominant causes of death were comorbidities, including cardiovascular diseases, tumors, and infections, while the most frequent pSS‐related causes of death were interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH). Male sex, older age, ILD, PAH, and high EULAR Sjögren's syndrome disease activity index (ESSDAI), thrombocytopenia, anemia, high immunoglobulin A (IgA) level, and glucocorticoid treatment independently increased the mortality risk, while using hydroxychloroquine was a protective factor. Conclusion Mortality rates have significantly increased in Chinese patients with pSS. Comorbidities, rather than pSS‐related organ damage, were the main causes of death. All‐cause mortality was associated with male sex, older age, ILD, PAH, high ESSDAI, thrombocytopenia, anemia, high IgA level, and glucocorticoid treatment, whereas hydroxychloroquine use might improve the long‐term survival.